Faktor-Faktor yang Berhubungan Kejadian Kekurangan Energi Kronik pada Ibu Hamil di UPTD Puskesmas Sungai Raya Aceh Timur Tahun 2024 - Rita Fauzia; Ester Simanullang; Retno Wahyuni (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The 2030 Sustainable Development Goals (SDGs) to end preventable newborn and under-five deaths with all countries striving to reduce the Neonatal Mortality Rate (NMR) to 12 per 1000 live births and reduce the Toddler Mortality Rate (IMR) to 25 per 1000 live births by 2030 (UNICEF, 2020). Based on the North Sumatra Central Bureau of Statistics, pregnant women who experienced SEZ in 2021 were 2,296 pregnant women, and in 2022 there was a decrease in the incidence of SEZ of 1,383 pregnant women, and in 2023 there was another increase of 1,765 pregnant women (BPS SUMUT, 2023). The type and design of quantitative analytical research through observational with case control study design is a study used to determine risk factors or health problems that are thought to have a close relationship with diseases that occur in the community. Age affects the occurrence of complications in third trimester pregnancy at Sungai Raya Health Center, East Aceh in 2024, where the results of the chi-square statistical test on maternal age are ρ = 0.006 <0.05. Parity affects the occurrence of complications in third trimester pregnancy at the Sungai Raya Health Center of East Aceh in 2024 where the results of the chi-square statistical test on parity are ρ = 0.020 <0.05. Gestational distance affects the occurrence of complications in third trimester pregnancy at the Sungai Raya East Aceh Health Center in 2024, where the results of data analysis using the chi-square test are ρ = 0.018 <0.05.